MEMBANGUN GENERASI SMART DAN BERKARAKTER PADA ANGGOTA KARANG TARUNA DESA SUKOWONO KECAMATAN JAYALOKA MELALUI POLA KOMUNIKASI YANG SANTUN - Tri Astuti; Nur Nisai Muslihah; Rusmana Dewi (LP4MK STKIP PGRI Lubuklinggau, 2022)
The ultimate goal of this PKM is to educate the younger generation of karang taruna members in understanding polite communication patterns for establishing a smart and character generation. This PKM was conducted for four weeks, starting from the preparation and initial observation until the evaluation and report. This program was conducted by counseling and socialization with implementation techniques using problem-solving, discussion, question & answer, and lecture. The total of participants was 36 people, including of 27 karang taruna members and 9 students of UNPARI who were doing KKN in Sukowono village, Jayaloka district. After the PKM Team conducted counseling and socialization, the participants began to understand and realize how importance of polite communication for establishing a smart and character generation. That was shown by participant's enthusiasm and responses during the program, as well as the results of the response questionnaires given by the PKM Team. About 35.6% and 52.8% of participants responded with good/appropriate answers and with very good/very appropriate answers respectively. Meanwhile, 11.6% of participants responded with mediocre/good enough answers